2023
DOI: 10.14336/ad.2022.1126
|View full text |Cite
|
Sign up to set email alerts
|

Driving Assessment for Persons with Dementia: How and when?

Abstract: Dementia is a progressive neurodegenerative disease leading to deterioration in cognitive and physical skills. Driving is an important instrumental activity of daily living, essential for independence. However, this is a complex skill. A moving vehicle can be a dangerous tool in the hand of someone who cannot maneuver it properly. As a result, the assessment of driving capacity should be part of the management of dementia. Moreover, dementia comprises of different etiologies and stages consisting of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…In a recent paper, Camilleri and Whitehead (2023) revised 44 observational studies and four meta‐analyses that investigated driving activities of persons with dementia. Most conclusions were of grade D evidence (poor quality) due to the inconclusive or inconsistent nature of the results, namely the significant variability in methodology and assessment measures used 10 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Camilleri and Whitehead (2023) revised 44 observational studies and four meta‐analyses that investigated driving activities of persons with dementia. Most conclusions were of grade D evidence (poor quality) due to the inconclusive or inconsistent nature of the results, namely the significant variability in methodology and assessment measures used 10 …”
Section: Resultsmentioning
confidence: 99%
“…The literature shows that some clinical signs in patients with dementia (Alzheimer's disease – AD) are associated with a worsened driving performance (Table 1). For instance, a recent review showed that inappropriate response to traffic stimuli, poor speed control, poor lane maintenance, and difficulty manoeuvring turns or intersections were traits found more consistently among drivers with dementia 10 …”
Section: Introductionmentioning
confidence: 99%